2019
DOI: 10.1016/j.jpsychires.2019.03.016
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic course of peripartum depression across pregnancy and childbirth

Abstract: Objective. Peripartum depression (PPD) pertaining to depression in pregnancy and postpartum is one of the most common complications around childbirth with enduring adverse effects on mother and child health. Although psychiatric symptoms may improve or worsen over time, relatively little is known about the course of PPD symptoms and possible fluctuations. Methods. We applied a person-centered approach to examine PPD symptom patterns across pregnancy and childbirth. 824 women were assessed at three time points:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 57 publications
(54 reference statements)
0
19
1
Order By: Relevance
“…Nonetheless, the severity of PND symptoms may significantly change over time in any population. In this study, 4.7% of women reported elevated PND symptoms over time, which is in contrast to previous studies [ 27 , 46 48 ]. For example, a study of 425 pregnant women in South Africa found two depression trajectories [ 48 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, the severity of PND symptoms may significantly change over time in any population. In this study, 4.7% of women reported elevated PND symptoms over time, which is in contrast to previous studies [ 27 , 46 48 ]. For example, a study of 425 pregnant women in South Africa found two depression trajectories [ 48 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The fit indices of the models generated through LGMM are reported in Table 2 . The four- class solution was excluded given that the solution had one class comprising less than 10 women [ 27 ]. The AIC and BIC values suggested that the three-class solution yielded the best fit while the entropy value favoured the two-class solution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations